Pengaruh Model Pembelajaran Reciprocal Teaching terhadap Keaktifan Belajar Peserta Didik Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII SMP Negeri 2 Pollung Tahun Pembelajaran 2023/2024 - Kartika Marbun; Baginda Sitompul; Tahadodo Waruwu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The aim of this research is to find out whether there is a difference in the learning activity of students who use the reciprocal teaching model compared to conventional ones in class VIII Christian Religious Education and Character education at SMP Negeri 2 Pollung for the 2023/2024 academic year. The research hypothesis is: